Transplantation Site Affects the Outcomes of Adipose-Derived Stem Cell-Based Therapy for Retinal Degeneration - Chengyu Hu; Huanzhi La; Xuancheng Wei; Yue Zhou; Qingjian Ou; Zhiyang Chen; Xiaoman Zhu; Jing-Ying Xu; Caixia Jin; Furong Gao; Juan Wang; Jingfa Zhang; et al. (Stem Cells International)
Adipose-derived stem cells (ASCs) have shown a strong protective effect on retinal degenerative diseases (RDD) after being transplanted into the subretinal space in an animal model. Recently, several clinical trials have been conducted to treat RDD with intravitreal transplantation of stem cells, including ASCs. However, the outcomes of the clinical trials were not satisfactory. To investigate if the transplantation site alters the outcome of stem cell-based therapy for RDD, we isolated rat ASCs (rASCs) and labeled them with green fluorescent protein. Autologous rASCs were grafted into the vitreous chamber or subretinal space in a rat RDD model induced by sodium iodate (SI). The electric response was recorded by ERG. The anatomic structure of the retina was observed in cryosections of rat eyes at posttransplantation weeks 1, 2, and 4. Neural retina apoptosis and epiretinal membrane- (ERM-) like structure formation were investigated by immunostaining. The intravitreal transplantation of rASCs resulted in an extinguished electric response, although the rosette formation and apoptosis of neural retina were reduced. However, the rASCs that grafted in the subretinal space protected the retina from the damage caused by SI, including a partial recovering of the electric response and a reduction in rosette formation. Intravitreally grafted rASCs formed a membrane, resulting in retina folding at the injection site. Müller cells, retinal pigment epithelial cells, and microglial cells migrated from the retina to the rASC-formed membrane and subsequently formed an ERM-like structure. Furthermore, vitreous fluid promoted rASC migration, and rASC-conditioned medium enhanced Müller cell migration as indicated by in vitro studies. These data suggested that the vitreous chamber is not a good transplantation site for ASC-based therapy for RDD and that a deliberate decision should be made before transplantation of stem cells into the vitreous chamber to treat RDD in clinical trials.